The softening of Chinese digital propaganda: Evidence from the People’s Daily Weibo account during the pandemic - Zhang, Chang; Zhang, Dechun; Shao, Hsuan Lei (Frontiers in Psychology, 2023)
Social media infuses modern relationships with vitality and brings a series of information dissemination with subjective consciousness. Studies have indicated that official Chinese media channels are transforming their communication style from didactic hard persuasion to softened emotional management in the digital era. This study explored the practices of the People’s Daily Weibo account from 2019 to 2021, COVID-19 is hardly normalized as it is still used as the justification for extraordinary measures in China. This study determined that People’s Daily Weibo account posts are undergoing softening, with the use of soft news, positive energy promotion, and the embedding of sentiment. Although COVID-19 temporarily increased the use of hard news, this only lasted through the initial stage of the pandemic. Emotional posts occupy a nonnegligible amount of the People’s Daily Weibo content. However, the majority of posts are emotionally neutral and contribute to shaping the authoritative image of the party press. Overall, the People’s Daily has softened their communication style on digital platforms and used emotional mobilization, distraction, and timely information provision to balance the party logic of building an authoritative media agency and the media logic of constructing audience relevance.